Rancang Bangun Emergency Changer Station Di Pantai Panmuti Desa Noelbaki - Theodorus De Rodath Kefi; Ishak S. Limbong; Yeremias M. Pell (Universitas Nusa Cendana, 2025)
This research focuses on the design and construction of a solar-based Emergency Charger Station at Panmuti Beach, Noelbaki Village, to meet the power needs of tourists who experience limited access to electricity. This system is designed with two monocrystalline solar panels with a maximum power of 50 WP connected in parallel, producing a total power of 100 W with a voltage of 17.2 V. The design includes measuring the intensity of solar radiation, calculating the power of the solar panels, the capacity of the Solar Charge Controller (SCC), and battery capacity. The battery with a total capacity of 36 Ah at 12 V allows daily energy storage of 800 Wh at an optimal sunlight intensity of 8 hours per day. Test results show that this system is effective in providing power to tourists' cellphones, although its efficiency is limited due to limited battery capacity. It is recommended to increase battery capacity and consider adding solar panels to increase the efficiency and sustainability of power supply at this tourist location.